Description of three species of Eurypon Gray, 1867 (Raspailiidae: Demospongiae: Porifera) from the Western Atlantic and a name to replace the the secondary homonym Eurypon topsenti - Cavalcanti, Thaynã; Santos, George Garcia; Pinheiro, Ulisses (Zootaxa, 2018)
Eurypon  Gray, 1867 comprises 49 valid species distributed worldwide, and in an extensive bathymetric range. Three Eurypon species are known for Brazil, all endemic from the Northeast region. Here, we describe three new species of Eurypon. Two of which are recorded from shallow waters (down to 100 m) off Pernambuco and Paraíba States, and one species is from deep waters (157 m) off Rio Grande do Norte State. Eurypon oxychaetum sp. nov. has large subtylostyles (1025–2125 µm, length), styles, two categories of acanthostyles and oxychaetes; Eurypon potiguaris sp. nov. has large tylostyles (1000–2315 µm, length), two categories of acanthostyles, and thin oxeas; Eurypon verticillatum sp. nov. is a blue sponge with exclusive verticillate acanthostyles. The new species were compared with all other Atlantic species of the genus. A replacement name for the secondary homonym Eurypon topsenti is proposed: Eurypon pulitzeri nom. nov. The presence of verticillate acanthostyles and oxychaetes spicules are reported for the first time in Table 1 genus.